EFFECTS OF DIGITAL ECONOMIC DEVELOPMENT ON AGRICULTURAL SECTOR CARBON EMISSION INTENSITY: PANEL DATA ANALYSIS IN DEVELOPED AND DEVELOPING COUNTRIES (Third Sector Social Economic Review, 2024)
The digital economy holds unique potential to accelerate agricultural development and reduce CO2 emissions in doing so. However, the accuracy of this argument needs to be tested. Therefore in this article, to investigate whether developments in the digital economy reduce agricultural carbon emissions, a panel data analysis was carried out, inspired by the STIRPAT model approach, which considers developed and developing countries separately. The research period covers the years 2002-2022. Based on the World Bank's Databank filter, 8 countries each from the high income group and upper-middle income group countries were included in the research. According to the research results, developments in the digital economy reduce CO2 emissions in the agricultural sector in both developed and developing countries.
Keywords: Agricultural carbon emissions; Digital economy; Economic complexity index; Environment; Panel Data Analysis